The value of intravoxel incoherent motion model-based diffusion-weighted imaging for predicting long-term outcomes in nasopharyngeal carcinoma - Qin, Yuhui; Chen, Chen; Chen, Haotian; Gao, Fabao (Frontiers in Oncology, 2022)
Objective: The aim of this study was to evaluate the prognostic value for survival of parameters derived from intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) in patients with nasopharyngeal carcinoma (NPC). Materials: Baseline IVIM-DWI was performed on 97 newly diagnosed NPC patients in this prospective study. The relationships between the pretreatment IVIM-DWI parametric values (ADC, D, D* and f) of the primary tumors and the patients' 3-year survival were analyzed in 97 NPC patients who received chemoradiotherapy. The cutoff values of IVIM parameters for LRFS were identified by non-parametric log-rank test. The local-regional relapse-free survival (LRRFS), local relapse-free survival (LRFS), regional relapse-free survival (RRFS), distant metastasis-free survival (DMFS), progression-free survival (PFS) and overall survival (OS) rates were calculated by using Kaplan-Meier method. Cox proportional hazards model was perfomed to explore the independent predictors for prognosis. Results: Ninety-seven participants (mean age, 48.4 years ± 10.5; 65 males) were analysed. Non-parametric log-rank test results showed that the optimal cutoff values of ADC, D, D* and f were 0.897×10-3 mm2 /s, 0.699 ×10-3 mm2 /s, 8.71 ×10-3 mm2 /s and 0.198%, respectively. According to the univariable analysis, the higher ADC group demonstrated significantly higher OS rates compared with the low ADC group (p = 0.036); the higher D group showed significantly higher LRFS and OS rates compared with the low D group (p = 0.028 and p = 0.017, respectively); the higher D* group exhibited significantly higher LRFS and OS than the lower D* group (p = 0.001 and p =0.002, respectively). Multivariable analyses indicated that ADC and D were the independent prognostic factors for LRFS (p = 0.041 and p = 0.037, respectively); D was an independent prognostic factor for LRRFS (p = 0.045); D* and f were the independent prognostic factors for OS (p = 0.019 and 0.029, respectively); f acted was an independent prognostic factor for DMFS (p = 0.020). Conclusions: Baseline IVIM-DWI perfusion parameters ADC and D, together with diffusion parameter D* could act as useful factors for predicting long-term outcome and selecting high-risk patients in NPC. Key words：Nasopharyngeal carcinoma; Chemoradiotherapy; Prognosis; Long-term outcome; Intravoxel incoherent motion; Diffusion-weighted imaging